2019
DOI: 10.1039/c9py00253g
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of polyethylene into a vitrimer by nitroxide radical coupling of a bis-dioxaborolane

Abstract: This work reports the synthesis and characterization of HDPE vitrimers obtained via reactive extrusion in the presence of bis-nitroxide dioxaborolanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
126
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 35 publications
5
126
0
Order By: Relevance
“…As previously observed, 15,21,56 PE vitrimer relinquishes an insoluble portion when placed in a good solvent. The insoluble portion of PE-v (PE-v-insol) was isolated using a method based on the ISO 10147 standard procedure.…”
Section: Isolation Of Insoluble and Soluble Portions Of Polyethylene supporting
confidence: 73%
“…As previously observed, 15,21,56 PE vitrimer relinquishes an insoluble portion when placed in a good solvent. The insoluble portion of PE-v (PE-v-insol) was isolated using a method based on the ISO 10147 standard procedure.…”
Section: Isolation Of Insoluble and Soluble Portions Of Polyethylene supporting
confidence: 73%
“…Determined by FTIR spectroscopy. b Error bars are the standard deviation of measurements from three different pieces of the sample.Isolation of insoluble and soluble portions of polyethylene vitrimer.As previously observed,15,21,56 PE vitrimer relinquishes an insoluble portion when placed in a good solvent. The insoluble portion of PE-v (PE-v-insol) was isolated using a method based on the ISO 10147 standard procedure.…”
supporting
confidence: 70%
“…The cross-links rearrange by engaging in a dioxaborolane metathesis exchange reaction. 15,21,56 Previously, we observed that strong interactions between the polymer backbone and cross-links induce PE vitrimer to adopt hierarchical meso-and nanostructures ( Figure 1). Essentially, PE vitrimer may be described as a phase separated blend with two distinct macrophases.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[14] Recently,N icolaþ, Leibler, and co-workers disclosed fascinating covalent exchangeable vitrimers crosslinked by dynamic exchange of boronate ester linkages,a lthough the actual exchange mechanism still remains unsolved. [24][25][26] To the best of our knowledge,n one of the dynamically crosslinked materials described so far reach the very high glass transition temperatures (T g above 200 8 8C) required for adhesives,p rotective coatings,l ow-wear,o rl ow-friction materials when exposed to high temperatures (contact with hot parts,c omposites for aerospace,e lectronics,b earings). Fors uch demanding applications,o nly af ew thermoplastics constituted of very rigid segments,w ith various degrees of solubility and processability are commercially available (for example,p olyaryletherketones,p olyethersulfones,p olyaramides,p olyetherimides,o rp olybenzimidazoles).…”
Section: Introductionmentioning
confidence: 99%